(untitled) (Global Journal of Medical Research, 2019)
Fibrous dysplasia belongs to a group of fibro-osseous lesions in which cellular fibrous connective tissue stroma replaces bone. It is a developmental hamartomatous lesion with cases occurring below the age of puberty. Fibrous dysplasia can occur as the monostotic form in which single bone is affected and polyostoticwhere multiple bones are involved. Majority of the cases reported are the monostotic form with the common site of involvement being the craniofacial skeleton. Polyostotic form are often associated with McCune-Albright syndrome, Jaffe-Lichtenstein syndrome and, Mazabraud syndrome. The syndromic lesions manifest as atriad of symptoms -fibrous dysplasias, endocrine abnormalities (endocrinopathies like precocious puberty and hypophosphatemia) and skin pigmentations (a cafe-au-lait spots). Fibrous dysplasias are expansile lesions and cause complications associated with the site of origin. The maxilla is the most common site of involvement in the craniofacial skeleton. In this case, a 13-year-old male patient presented who was having maxillary fibrous dysplasia.